Five gold rings eaudiobook A totally hilarious and unforgettable christmas rom-com. - Bailey, Kristen (Storm Publishing, 2023)
" Obsessed... read in one day... One of the best romcoms I've ever read ." Reader review, ⭐⭐⭐⭐⭐ Five gold rings. Delivered to the wrong addresses. Five Christmas proposals and weddings ruined. Unless Eve can save the day...? As Christmas lights twinkle around London, twenty-eight-year-old Eve arrives home ready to celebrate her favourite holiday, only to find... her boyfriend in the shower with a pretty blonde. Heartbroken, Eve throws the gifts she's selflessly bought and wrapped for HIS family out of the window, then heads to Caspars' Jeweller's, where she works, for some tea and sympathy. But there she discovers another drama unfolding; five rings have gone AWOL, and unless she can track them down and deliver them to their rightful owners five perfectly planned festive weddings and proposals will end in disaster. Eve's colleague Joe – moonlighting as a naked butler at a Christmas party – races to assist on her wild goose chase across London, dressed as a sexy elf. Together they set off on a mission to save Christmas. And along the way, just maybe, some of that festive cheer and romance might rub off on Eve and Joe, and help heal Eve's broken heart... An utterly hilarious novel for anyone looking for festive romance with all the feels. If you have a hot date with Love Actually every Christmas you will adore this gloriously funny and unmissable festive read. Readers are obsessed with Five Gold Rings: " I LOVED IT!!! " Reader review, ⭐⭐⭐⭐⭐ " Absolutely adorable must-read Christmas romance . One of those stories that takes you along for the journey, captivates you, brings you laughter, warm fuzzies, gives you hope and leaves you smiling." Reader review, ⭐⭐⭐⭐⭐ " Oh my god! This is one hilariously good Christmas read! I just loved everything about it... Definitely one of the best Christmas books I have read! Loved it!" Reader review, ⭐⭐⭐⭐⭐ "A frank funny festive feel-good read! Had me laughing from start to finish ." Reader review, ⭐⭐⭐⭐⭐ "The perfect holiday read to have you smack in your feels and laughing hysterically!" Reader review, ⭐⭐⭐⭐⭐ " I loved this book! From beginning to end, it was absolutely hysterical." Reader review, ⭐⭐⭐⭐⭐ "I absolutely loved this Christmas romcom! It made me laugh out loud so many times! I can't stop laughing... Definitely made me LOL but it also made me unexpectedly cry too because that's how good this book was. It took me on an emotional journey and that deserves 5 GOLD STARS !" Reader review, ⭐⭐⭐⭐⭐ "Pure reading escapism. Had me laughing the whole time, with tears of laughter and joy ." Reader review, ⭐⭐⭐⭐⭐ "Loved this. A book that you can get wrapped up cosy in a blanket with and read all day long getting you into that romantic Christmas spirit." Reader review, ⭐⭐⭐⭐⭐ " The perfect Christmas romcom ... had me laughing out loud." Reader review, ⭐⭐⭐⭐⭐ "Such a fun wild ride... An utter delight ." Reader review, ⭐⭐⭐⭐⭐